Induksi Kalus dari Hipokotil Belimbing Merah (Baccaurea angulata) dengan Penambahan 2,4-D (Dichlorophenoxy Acetic Acid) dan BAP (6-Benzyl Amino Purin) - Teresia, Novi; Zakiah, Zulfa; Turnip, Masnur (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Red starfruit is one of the endemic plants of Kalimantan which produces secondary metabolites which has been empirically used as antioxidant, antibacterial, and anticancer. This plant has a long reproductive period and seedless fruit is often found during the fruiting season, which is a problem for the sustainability of the red starfruit in nature. Conservation of red star fruit for propagation and production of secondary metabolites can be done in vitro through callus culture. This research aims to determine the effect of adding the growth regulators dichlorophenoxy acetic acid (2,4-D) and 6-benzyl amino purine (BAP) on callus induction time, percentage of callus forming explants, callus color and texture, and callus growth. This research used a Completely Randomized Design (CRD) with a factorial pattern consisting of two treatment factors, namely 2,4-D (0; 0.25; 0.5; 0.75; 1 ppm) and BAP (0; 0.25; 0.5; 0.75; 1 ppm). The percentage of explants forming callus (%), the time the callus appeared (days after planting), the color and texture of the callus, the wet weight and dry weight of the callus (g) were research observation parameters.The results showed that the single factor 2,4-D, single factor BAP, and the interaction of 2,4-D and BAP had a significant effect to callus appearance time. Single administration of 2,4-D and BAP had a significant effect on callus dry weight. The color variations of the callus produced are white, green and brown with a compact texture. The fastest callus emergence time was at 11.00 days after planting (DAP), namely in the combination treatment of 1 ppm 2,4-D and 0.75 ppm BAP, single treatment 0.75 ppm and 1 ppm 2,4- D. The highest average dry weight of 0.024 g was obtained in the single treatment of 0.75 ppm BAP.